Investigating factors influencing decision-making around use of breastmilk substitutes by health care professionals: a qualitative study - Maisha Islam; Dourra Assani; Serine Ramlawi; Malia SQ Murphy; Kameela Miriam Alibhai; Ruth Rennicks White; Alysha LJ Dingwall-Harvey; Sandra I Dunn; Darine El-Chaâr (BMC, 2024)
Abstract Background Breastfeeding is recognized as the gold standard of infant feeding and nutrition. The World Health Organization recommends exclusive breastfeeding (EBF) of infants for the first 6 months of life. A variety of factors may impact breastfeeding practices in-hospital which may continue after hospital discharge, such as the use of breastmilk substitutes (BMS). The Baby-Friendly Initiative (BFI), which aims to promote and support breastfeeding practices, established a target rate of 75% for EBF from birth to hospital discharge. Currently, this target is not being met at The Ottawa Hospital (TOH), indicating there is room for improvement in EBF rates. The purpose of this study is to explore health care professionals (HCP) decision-making around use of BMS and identify factors that drive the use of BMS with and without medical indications. Methods In this qualitative study, semi-structured interviews were conducted with HCPs within TOH from January to June 2022. All participants had experience in maternity or postpartum care and were probed on factors influencing use of BMS at this institution. Interview transcripts were coded using an inductive approach. Results A total of 18 HCPs were interviewed including physicians, midwives, lactation consultants, and registered nurses. Multilevel barriers influencing the use of BMS were categorized into patient, HCP, and institution-level factors. Subthemes that emerged ranged from parental preferences, training differences amongst HCPs, to budget and staffing issues. Over half of HCPs were prepared to answer questions on EBF and were familiar with the BFI. Although most were supportive of this institution receiving BFI designation, a few providers raised concerns of its impact on parents who would like to supplement. Conclusions Several modifiable factors influencing decision-making for use of BMS were identified. These findings will be used to inform unit leads, help identify effective strategies to address modifiable barriers, and develop tailored breastfeeding supports to improve EBF rates.